2011
DOI: 10.1111/j.1442-200x.2011.03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Language assessment of non‐handicapped twins at 5 years of age

Abstract: It is hoped that the present findings could lead to a more precise assessment of children for speech impairment and, above all, to more efficient preventive intervention. Whatever mechanisms are involved, the present results indicate that twins born as a result of IVF, are at a disadvantage in terms of language development in comparison with spontaneously conceived twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…Clinically, speech language pathologists and teachers should take into account these small differences in language development when working with twins. These results are in accordance with recent studies [3,4,5] in younger children. Language in these studies was investigated using questionnaires, psychological batteries or simple language tests.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Clinically, speech language pathologists and teachers should take into account these small differences in language development when working with twins. These results are in accordance with recent studies [3,4,5] in younger children. Language in these studies was investigated using questionnaires, psychological batteries or simple language tests.…”
Section: Discussionsupporting
confidence: 83%
“…Monozygotic twins and boys had lower scores than dizygotic twins and girls. Gucuyener et al [5] investigated expressive vocabulary in 5-year-old term and preterm twins and singletons and found that even after excluding most premature twins, twins performed worse than singletons.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Gucuyener et al . () indicate that twins born as a result of IVF are at a disadvantage in terms of language development in comparison with spontaneously conceived twins. However, it is not clear which mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Singletons scored significantly better for all language skills. Gucuyener et al (2011) investigated language development of twins and found a language delay of 3 months in term IVF twins compared with term IVF singletons. In the literature it has been shown that language development of twins is slightly different compared with singletons , Hay et al 1987.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of boy-girl twins, the girls scored higher than their brothers in six out of seven cases. These results were not surprising; studies have shown that one twin is usually stronger than the other in verbal skills in their native language (Gucuyener et al, 2011) and that girls develop oral proficiency as much as 1 year ahead of boys (Gurian & Stevens, 2011). In their study, Gucuyener et.…”
Section: Discussionmentioning
confidence: 93%